2009
DOI: 10.1007/s10689-009-9286-0
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between a family history of colorectal cancer and survival of patients with colorectal cancer

Abstract: The purpose was to analyze survival of patients with colorectal cancer and a positive family history for colorectal cancer in first degree relatives compared with those with no such family history and to determine whether differences in survival could be explained by known clinico-pathological factors. During 2000-2003, 318 consecutive patients with colorectal cancer answered a written questionnaire about their family history for colorectal cancer. During a 6-year follow-up, recurrences and survival were regis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 32 publications
1
29
0
Order By: Relevance
“…In five of these, a positive family history of CRC was associated with better survival in CRC patients [6,9,[11][12][13][14]. Two studies indicated higher mortality [8,15], and six studies found no association between CRC family history and survival in CRC patients [5,7,9,10,16,17], although Slattery et al [7] did find a higher mortality for men under age 55 with a positive family history of CRC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In five of these, a positive family history of CRC was associated with better survival in CRC patients [6,9,[11][12][13][14]. Two studies indicated higher mortality [8,15], and six studies found no association between CRC family history and survival in CRC patients [5,7,9,10,16,17], although Slattery et al [7] did find a higher mortality for men under age 55 with a positive family history of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies indicated higher mortality [8,15], and six studies found no association between CRC family history and survival in CRC patients [5,7,9,10,16,17], although Slattery et al [7] did find a higher mortality for men under age 55 with a positive family history of CRC. Only one small study (N = 318) [12] verified the FDR's cancer diagnoses as reported by the patients, the rest relied solely on self-report of cancer. At least two studies on accuracy of self-reported family history have found that CRC diagnoses in relatives often are underreported [26,27], which stresses that the use of selfreported cancer among family members can cause misclassification.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, family history has also been associated with improved survival after treatment for CRC. In one Swedish study, patients with one first-degree relative with CRC were 75% less likely to succumb to their disease [9]. This is somewhat counter-intuitive to what is expected, as patients with a positive family history should be more prone to developing polyps and metachronous cancers.…”
Section: Review Articlementioning
confidence: 94%